Mitigating Groundwater Depletion in North China Plain with Cropping System that Alternate Deep and Shallow Rooted Crops - Yang, Xiao-Lin; Chen, Yuan-Quan; Steenhuis, Tammo S.; Pacenka, Steven; Gao, Wang-Sheng; Ma, Li; Zhang, Min; Sui, Peng (Frontiers in Plant Science, 2017)
In the North China Plain, groundwater tables have been dropping at unsustainable rates of 1 m per year due to irrigation of a double cropping system of winter wheat and summer maize. To reverse the trend, we examined whether alternative crop rotations could save water. Moisture contents were measured weekly at 20cm intervals in the top 180 cm of soil as part of a 12-year field experiment with four crop rotations: sweet potato→ cotton→ sweet potato→ winter wheat–summer maize (SpCSpWS, 4-year cycle); peanuts → winter wheat–summer maize (PWS, 2-year cycle); ryegrass–cotton→ peanuts→ winter wheat–summer maize (RCPWS, 3-year cycle); and winter wheat–summer maize (WS, each year). We found that, compared to WS, the SpCSpWS annual evapotranspiration was 28% lower, PWS was 19% lower and RCPWS was 14% lower. The yield per unit of water evaporated improved for wheat within any alternative rotation compared to WS, increasing up to 19%. Average soil moisture contents at the sowing date of wheat in the SpCSpWS, PWS and RCPWS rotations were 7%, 4%, and 10% higher than WS, respectively. The advantage of alternative rotations was that a deep-rooted crop of winter wheat reaching down to 180 cm followed shallow rooted crops (sweet potato and peanut drawing soil moisture from 0-120 cm). They benefitted from the sequencing and vertical complementarity of soil moisture extraction. Thus, replacing the traditional crop rotation with cropping system that involves rotating with annual shallow rooted crops is promising for reducing groundwater depletion in the North China Plain.